Investigating the Application of N,N’-Disubstituted-1,8-Diamidonaphthalene as a Ligand in Transition Metal and Main Group Chemistry - Almalki, Nawal (Université d'Ottawa / University of Ottawa, 2018)
This thesis focuses on the design and development of novel versatile diamido ligands for transition metal and main group element chemistry. The central concept of this work deal relied on the design of N, N'-disubstituted-1,8-diaminonaphthalene (H2RR’-DAN) as proligands to dianionic diamido ligand scaffolds. These ligands would then be employed for stabilization of main group element (e.g. Li, B, Al) and transition metal (e.g. Ti, Zn) compounds.
Keywords: Main group element; N, N'-disubstituted-1,8-diaminonaphthalene